The Caloplaca holocarpa group in the Nordic countries, except Iceland - Arup, Ulf (The Lichenologist, 2009)
The Caloplaca citrina group in the Nordic countries, except Iceland, is analysed with regard to morphology, anatomy, ecology, and chemistry. Their genetic relationship is also analysed using the ITS ribosomal DNA gene. The results show that there are at least five species within what has been called C. citrina, of which four are closely related to one another and to several non-sorediate species. Three of these, C. citrina, C. flavocitrina and C. arcis have previously been recognized at specific or varietal level some time during the last two centuries, whereas the fourth species, C. dichroa, is described as new. The fifth species, C. phlogina, is not related to the other species but shows a close relationship to the Xanthoria candelaria group. The species are described and illustrated in colour. Distribution maps are given for the study area and a key to sorediate, yellow to orange species occurring in the Nordic countries, except Iceland, is also provided.